2016
DOI: 10.1007/s10147-016-0949-1
|View full text |Cite|
|
Sign up to set email alerts
|

Atypical and malignant granular cell tumors in Japan: a Japanese Musculoskeletal Oncology Group (JMOG) study

Abstract: MGCTs have high rates of recurrence and metastasis including lymph node metastasis. As histologically atypical cases also have metastatic potential, close attention should be paid to AGCTs. The combination of histological evaluation and tumor size may lead to more accurate diagnosis of this rare neoplasm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
27
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 17 publications
3
27
1
1
Order By: Relevance
“…This study confirmed characteristics of GCT as well as its management previously described in published reports such as a predilection to affect females more often than males, occurrence in a wide variety of locations, and excision alone as the primary treatment . Benign GCT appears to occur most often in the head neck region, while, as found in this study, malignant GCT occurs most frequently in the soft tissues and skin …”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This study confirmed characteristics of GCT as well as its management previously described in published reports such as a predilection to affect females more often than males, occurrence in a wide variety of locations, and excision alone as the primary treatment . Benign GCT appears to occur most often in the head neck region, while, as found in this study, malignant GCT occurs most frequently in the soft tissues and skin …”
Section: Discussionsupporting
confidence: 92%
“…As mentioned above, the primary treatment of GCT has traditionally been surgical excision, without regional lymphadenectomy . Although seldom reported in the literature, lymph node dissection does occur.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations